ATIM-37. SAFETY RUN-IN RESULTS OF A PHASE I/II STUDY TO EVALUATE THE SAFETY AND CLINICAL EFFICACY OF ATEZOLIZUMAB (ATEZO; aPDL1) IN COMBINATION WITH TEMOZOLOMIDE (TMZ) AND RADIATION IN PATIENTS WITH NEWLY DIAGNOSED GLIOBLASTOMA (GBM). (5th November 2018) - Weathers, Shiao-Pei; Kamiya-Matsuoka, Carlos; Dervin, Shannon; Yun, Cindy; Loghin, Monica; O'Brien, Barbara; Harrison, Rebecca; Yung, W K Alfred; Penas-Prado, Marta; de Groot, John
Abstract: BACKGROUND: Immunotherapy strategies like PD-1/PD-L1 inhibition may work synergistically with radiation, which has been shown to increase antigen presentation and promote a pro-inflammatory tumor microenvironment. This trial evaluated the safety of concurrent atezo with radiation therapy and TMZ followed by adjuvant TMZ and atezo in newly diagnosed GBM patients. METHODS: Eligibility criteria included patients with newly diagnosed GBM age ≥ 18 yrs who have undergone only surgery. The primary objective of the phase I safety run-in was to evaluate atezo in combination with radiation and TMZ during the concurrent stage and in combination with TMZ during the adjuvant stage. RESULTS: 11 patients were accrued in the concurrent safety run-in phase. 2 dose-limiting toxicities (DLT) were observed in 1 patient who developed both grade 3 hepatitis and pneumonitis related to atezo. 2 patients discontinued treatment during the concurrent stage due to medical complications deemed unrelated to study drug. In the 8 evaluable patients who completed the concurrent phase, no other grade 3 or 4 atezo-related toxicities were observed. 5 of the 8 evaluable patients completed the combination treatment without the need for dexamethasone. The remaining 3 of the 8 evaluable patients required no more than 4 mg daily of dexamethasone during combination treatment. All 8 patients had stable MRI findings following completion of the concurrent phase. 7 of the 8 evaluable patients proceeded with adjuvant treatment with atezo and TMZ with no grade 3 or 4 atezo-related toxicities observed to date (no. cycles range, 1–6). CONCLUSIONS: Concurrent use of atezo with radiation and TMZ was tolerable, and no new safety signals were noted. The majority of evaluable patients were able to complete the combination treatment without the need for concurrent steroid administration. The phase II component of the trial is recruiting patients (n=50) to evaluate clinical efficacy.